2008
DOI: 10.1103/physrevb.77.085211
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the triplet diffusion and quenching rates in films of anIr(ppy)3-cored dendrimer

Abstract: We study photoluminescence and triplet-triplet exciton annihilation in a neat film of a fac-tris͑2-phenylpyridyl͒iridium͑III͒ ͓Ir͑ppy͒ 3 ͔-cored dendrimer and in its blend with a 4 , 4Ј-bis͑N-carbazolyl͒biphenyl host for the temperature range of 77-300 K. The nearest neighbor hopping rate of triplet excitons is found to increase by a factor of 2 with temperature between 150 and 300 K and is temperature independent at lower temperature. The intermolecular quenching rate follows the Arrhenius law with an activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Ribierre et al observed a similar temperature dependence of the time-averaged hopping rate of triplet excitons in phosphorescent iridium-cored metal–ligand charge transfer complexes using triplet–triplet annihilation. 122 …”
Section: Excitation Energy Transfer To Heterojunctionmentioning
confidence: 99%
“…Ribierre et al observed a similar temperature dependence of the time-averaged hopping rate of triplet excitons in phosphorescent iridium-cored metal–ligand charge transfer complexes using triplet–triplet annihilation. 122 …”
Section: Excitation Energy Transfer To Heterojunctionmentioning
confidence: 99%
“…4,4-Bis(carbazol-9-yl)-2,2-biphenyl (CBP, Scheme 1) is a typical host molecule of the luminescent layer. While there have been many experimental studies on the photo-luminescent properties of Ir(ppy) 3 in a CBP layer [17][18][19][20], no geometrical structure has been reported for the mixture of Ir(ppy) 3 and CBP. Thus it is necessary to assume some reasonable orientation in the amorphous layer.…”
Section: Introductionmentioning
confidence: 97%
“…This dendrimer was chosen for these measurements because its basic photophysical properties have been intensively studied in the past and are well documented. 12,14,15,19 An excitation wavelength of 325 nm was used in this case to get sufficient absorbance. The PLQY of the 180 nm thick film was found to be 68 AE 7%, dropping to 54 AE 5% and 29 AE 3% for film thicknesses of 140 and 60 nm respectively.…”
Section: Thickness Dependence Of the Phosphorescencementioning
confidence: 99%
“…In this paper, we explore surface quenching of phosphorescence in films of several fac-tris(2-phenylpyridyl)iridium(III) [Ir(ppy) 3 ]-cored dendrimers with different spacing between them, with the spacing controlled by the structure of the dendrimer as well as by blending with a large optical gap host. [14][15][16][17][18][19] The molecular structures of the first generation [Ir(ppy) 3 ]-cored dendrimers used in this work are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%